2017
DOI: 10.1097/iae.0000000000001265
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Photoreceptor Reflectivity Through Multimodal Imaging of Outer Retinal Tubulation in Advanced Age-Related Macular Degeneration

Abstract: Purpose To investigate the microscopic structure of outer retinal tubulation (ORT) and optical properties of cone photoreceptors in vivo, we studied ORT appearance by multimodal imaging, including spectral domain optical coherence tomography (SD-OCT) and adaptive optics scanning laser ophthalmoscopy (AOSLO). Methods Four eyes of 4 subjects with advanced AMD underwent color fundus photography, infrared reflectance imaging, SD-OCT, and AOSLO with a high-resolution research instrument. ORT was identified in clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…Zweifel et al[13] first reported these characteristic structures in OCT images acquired from subjects with age-related macular degeneration,[13] while recent work by Litts et al revealed that the branching, interconnected structure of ORTs is composed of degenerating cones and infolded ELM. [14] Consistent with recent results published by Litts et al .,[27] ORTs did not display IZ/EZ bands on SD-OCT or recognizable cone reflectivity on confocal imaging. However, we did observe remnant cone inner segments in these structures using split-detector imaging.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Zweifel et al[13] first reported these characteristic structures in OCT images acquired from subjects with age-related macular degeneration,[13] while recent work by Litts et al revealed that the branching, interconnected structure of ORTs is composed of degenerating cones and infolded ELM. [14] Consistent with recent results published by Litts et al .,[27] ORTs did not display IZ/EZ bands on SD-OCT or recognizable cone reflectivity on confocal imaging. However, we did observe remnant cone inner segments in these structures using split-detector imaging.…”
Section: Discussionsupporting
confidence: 88%
“…[12, 1726] Indeed, confocal AOSLO has recently been used to document lack of cone reflectivity in the ORTS found in age-related macular degeneration. [27] In choroideremia, AOSLO imaging has uncovered novel pathologic features including bubble-like lesions that appear to co-localize to structures in the choroid visualized by SD-OCT[26] and yielded results suggesting a primary RPE degeneration with subsequent loss of photoreceptors and choroid. [12, 26] Recent work by Morgan et al showed an abrupt decline in confocal AOSLO photoreceptor reflectivity in areas of RPE degeneration[26], while SD-OCT imaging revealed interdigitation zone (IZ, thought to represent the junction of photoreceptors and RPE) dropout and RPE thinning prior to disruptions in the overlying EZ.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of ORTs shows that cones may survive for a relatively long duration in atrophic areas. Fundus camera and scanning AOO can both detect the outlines of ORTs (figure 13) 55 . It has been shown that scanning AOO can detect cone structure within ORTs 56 .…”
Section: Outer Retinal Tubulationsmentioning
confidence: 99%
“…79,[102][103][104][105][106] ORTs appear on OCT B-scans as circular or ovoid structures in the outer nuclear layer, which may show a branching morphology with en face OCT reconstruction. The hyporeflective lumen of ORTs is delimited by a hyperreflective band representing the ELM.…”
Section: Outer Retinal Tubulationsmentioning
confidence: 99%